Heterosis in Simmental Angus rotational-cross calves - L.A. Kriese; R.R. Schalles; Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1986)
Heterosis estimates were determined for gestation length, birth weight, and yearling weight using a two-breed rotational crossbreeding system with Angus and Simmental cattle. Heterosis for gestation length was -.3%; birth weight, 8.31%; weaning weight 5.05%, and yearling weight, 5.39%. Angus-sired calves from Simmental darns were significantly heavier at weaning and as yearlings than the reciprocal cross.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Heterosis; Gestation length; Birth weight; Yearling weight